The association between smartphone addiction and self-esteem among physical education undergraduate students: The chain-mediating roles of professional identity and meaning in life - Pu Sun; Mingyue Cui; Xi Chen; Ling Yan (PLoS ONE, 2026)
This study investigated the associations between smartphone addiction and self-esteem among undergraduate Physical Education students, focusing on the mediating roles of professional identity and meaning in life. A total of 695 undergraduate students majoring in Physical Education were recruited through a convenience sampling method from a sports university in Beijing. Participants completed the Smartphone Addiction Scale, the Professional Identity Scale for Pre-service Teachers, the Meaning in Life Questionnaire, and the Rosenberg Self-Esteem Scale. Structural equation modelling (SEM) was conducted in Mplus 8.3 to test multiple and chain mediation effects. Model fit indices indicated an acceptable fit (χ²/df = 4.43, CFI = 0.96, TLI = 0.93, RMSEA = 0.08). The results showed that smartphone addiction was significantly and negatively associated with professional identity ( β = –0.42, 95% CI [–0.51, –0.32], p < 0.001) and meaning in life ( β = –0.29, 95% CI [–0.38, –0.19], p < 0.001), both of which were positively associated with self-esteem (professional identity: β = 0.36, 95% CI [0.25, 0.46], p < 0.001; meaning in life: β = 0.31, 95% CI [0.21, 0.42], p < 0.001). Smartphone addiction was also directly and negatively associated with self-esteem ( β = –0.27, 95% CI [–0.37, –0.18], p < 0.001). Mediation analyses further indicated that professional identity and meaning in life independently and sequentially mediated this association, forming a significant chain-mediating pathway (total indirect effect = –0.047, 95% CI [–0.071, –0.029]). The final model accounted for 38.2% of the variance in self-esteem ( R ² = 0.382). These findings highlight the psychological mechanisms linking smartphone addiction and self-esteem, offering evidence-based implications for interventions addressing smartphone overuse among Physical Education undergraduates.